Analisis Pengelolaan Mutu Pelayanan Loket Pendaftaran Pasien Rawat Jalan di Puskesmas Bulakamba - Iim Al Imron; Sri Rejeki (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The outpatient registration site is the frontline service unit for each community health center. Bulakamba Community Health Center has several problems, including a backlog of patients, a delayed registration process and long patient waiting times. The aim of this research is to analyze the management of service quality at the outpatient registration counter at the Bulakamba Community Health Center. The type of research is qualitative research using phenomenological methods. There were 8 research informants selected using purposive sampling technique. Data collection techniques use interviews and observation. The research results show that the quality of Bulakamba Community Health Center services in terms of Input and Output is good and meets standards, but the quality of the Process is still problematic. Problems with the quality of services at the Bulakamba Community Health Center include long waiting times and the poor performance of health service staff.